The Image of a Lithuanian and a Samogitian in the Cultural Press of Warsaw in Late 1800s. The (non-)stereotyped Case of Nikodem Erazm Iwanowski, the Landlord of a Small Manor - Židonis, Giedrius (Respectus Philologicus, 2019)
At the end of July 1885, Nikodem Erazm Iwanowski, the landlord of a small manor in Samogitia, brought his son to Warsaw for studies, and spent two years there. He maintained correspondence with Eliza Orzeszkowa, became acquainted with the poetess Maria Konopnicka, himself wrote poetry and prose, and painted. However, in his letters, he wrote that, being a newcomer from the province, he felt somewhat clumsy and uncomfortable. This confession encouraged the author of the present paper to review the cultural press of Warsaw published during the 1880s. The aim of the review was to investigate in which context Lithuanians/Samogitians were mentioned and how depicted, and to determine whether the fiction published in the aforementioned press contained satirical characters associated with Lithuania/Samogitia. The investigation revealed a number of publications about Lithuania/Samogitia – for example, descriptions of travels and places. Here we can find stereotypical pictures of Lithuanians and Samogitians. The investigation also revealed the presence of fiction containing satirical, comical depictions of Lithuanians or Samogitians. Here, two plotlines may be identified: characters in a foreign land, and characters in a large city
Keywords: Samogitia; 19th century; positivism; press; Nikodem Erazm Iwanowski